2D Ferrous Ion‐Crosslinked Ti3C2Tx MXene Aerogel Evaporators for Efficient Solar Steam Generation. (4th October 2021) - Li, Xiao‐Peng; Li, Xiaofeng; Li, Heguo; Zhao, Yue; Li, Wei; Yan, Shouke; Yu, Zhong‐Zhen
Abstract: Although solar‐driven water evaporation technology is promising for desalination of seawater and purification of wastewater, it is still an issue to enhance the solar steam generation performances by efficient utilization of sustainable solar energy. Herein, 2D ferrous ion‐crosslinked Ti3 C2 T x MXene‐based aerogel films (MAFs) are fabricated as efficient solar steam generation devices by vacuum‐assisted filtration of aqueous dispersions of MXene with FeCl2 followed by freeze‐drying. The strong interaction of ferrous ions with –OH groups of MXene sheets and the freeze‐drying process are crucial for constructing structurally stable porous films with rough surfaces. Benefiting from the strong solar light absorption capacity and high solar‐thermal energy conversion efficiency of MXene sheets, along with the hydrophilic and structurally stable porous architecture of MAFs, the average evaporation rates of an optimal MAF evaporator are as high as 1.67 and 14.52 kg m −2 h −1 with evaporation efficiencies of 94.3% and 91.7% under solar light irradiations of 1 and 10 kW m ‐2, respectively. As a promising solar steam generation device, the 2D porous and hydrophilic MAF evaporator is highly efficient in generating clean water from both natural seawater and organic wastewater with satisfactory ion rejection efficiencies of close to 100%. Abstract : A ferrous ion‐crosslinked MXene‐based aerogel film is efficient in generating clean water from both seawater and organic wastewater. Its average evaporation rates are as high as 1.67 and 14.52 kg m −2 h ‐1 with evaporation efficiencies of 94.3% and 91.7% under 1‐sun and 10‐sun irradiation, respectively.